The integration of natural resource management into the curriculum of rural under-resourced schools : a Bernsteinian analysis - Nsubuga, Yvonne Nakalo (Rhodes University, Faculty of Education, Department of Education, 2010)
This study was motivated by the need to improve curriculum relevance in poor rural schools through contextualised teaching and learning based on the management of local natural resources. It involved four schools which are located in the Ngqunshwa Local Municipality of the Eastern Cape Province of South Africa. The study's aim was to provide insight into and better understanding of the curriculum implementation process regarding natural resource management (NRM) education in a poor rural education context. This was done by analysing the extent of NRM integration in pedagogic texts, activities and practices in the different fields which constitute the structure of the pedagogic system in this education sector. The study adopted an interpretivist approach to the analysis, which was based on indicators of the extent of NRM integration, and was informed by Bernstein's concepts of classification and curriculum recontextualisation, and his model of the structure of the pedagogic system. The items which were analysed included national and provincial Grade 10 Life Sciences curriculum documents, Grade 10 Life Sciences textbooks, in-service training workshops for Life Sciences teachers, and various school documents, activities and practices. The analysis also involved interviews with educators, and classroom observations of Grade 10 Life Sciences lessons. The results revealed a very high overall level of NRM integration in the Grade 10 Life Sciences curriculum documents produced at national and provincial levels. The overall level of NRM integration was also found to be very high in the Grade 10 Life Science textbooks that were analysed, but very low in the in-service teacher training workshops, and in the schools' documents, activities and practices, especially in the Grade 10 Life Sciences lessons, and in schools' end-of-year Grade 10 Life Sciences examination papers. The study makes a number of recommendations towards effective integration of NRM into the curriculum of Eastern Cape's rural poor schools which include more specific and explicit reference to NRM in the official Grade 10 Life Sciences curriculum documents, the provision of environmental education courses to district education staff and Grade 10 Life Sciences teachers, the training of teachers in the classroom use of textbooks and other educational materials, and regular monitoring of teachers' work. The study also exposes important knowledge gaps which need urgent research attention in order to enhance NRM education in the poor rural schools of the Eastern Cape. These include analysing power and control relationships between the various agencies and agents that are involved with curriculum implementation in this education sector, and conducting investigation into the creation of specialist NRM knowledge and into the quality of NRM knowledge that is transmitted as pedagogic discourse in schools. This study contributes to the fields of rural education and environmental education in South Africa, and to the growing interest in the study of curriculum from a sociology of education perspective in the context of the country's post-apartheid curriculum reforms.
Keywords: Conservation of natural resources -- Study and teaching -- South Africa; Environmental education -- Curricula -- South Africa -- Eastern Cape; Bernstein, Basil B; Nature conservation -- Study and teaching